2004
DOI: 10.1159/000081636
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences of Lens Transparency Properties with Aging and Prevalence of Age-Related Cataract Applying a WHO Classification System

Abstract: Purpose: To investigate racial differences of lens transparency properties and the prevalence of lens opacification by age. Methods: Lenses of randomly selected Asian (1,038 Japanese and 517 Singaporeans) and Caucasian (1,045 Icelanders) subjects were evaluated for their lens transparency property (LTP). The prevalence of lens opacification was determined with a newly proposed WHO cataract classification system. Results: LTP increased with aging for all nationalities. Light scattering intensity was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Epidemiological studies using slit lamp and Scheimpflug camera observations have shown that, in temperate regions of the world, cortical cataract is by far the most prevalent age-related cataract, about four times more common than nuclear opacification [41,87,88].…”
Section: Age-related Cataract (A) Forms Of Cataractmentioning
confidence: 99%
“…Epidemiological studies using slit lamp and Scheimpflug camera observations have shown that, in temperate regions of the world, cortical cataract is by far the most prevalent age-related cataract, about four times more common than nuclear opacification [41,87,88].…”
Section: Age-related Cataract (A) Forms Of Cataractmentioning
confidence: 99%
“…The prevalence of the 3 main types of age-related cataracts differs in different regions of the world and in different racial groups [5] . However, in all areas and populations, PSCs are least common.…”
mentioning
confidence: 99%
“…The lens transparency property in diabetic patients who have a predisposition for cataract is said to be higher than that in nondiabetic patients. 13 We also compared the lens transparency property in Icelandic, Japanese, and Singaporean subjects with transparent lenses 14 and found that the property in Singaporeans, whose incidence of cataract is significantly higher than that in Icelanders and Japanese, significantly exceeded that in the other 2 groups and that lens transparency property is an appropriate index of aging change of the entire lens. In this study, we found a significant correlation between lens transparency property and retinal image contrast.…”
Section: Discussionmentioning
confidence: 99%